Effectiveness of trans-arterial embolisation of liver neuroendocrine tumour metastases. (13th March 2011) - Mandair, D S; Bridgestock, H; Shah, T; Mangat, K; Olliff, S; Mahon, B; Hussain, S; Johnson, P; Palmer, D
Abstract : Introduction: Neuroendocrine tumours (NET) with liver metastases have a poor prognosis and are difficult to palliate. Transarterial embolisation (TAE) is increasingly used to improve symptoms and reduce tumour size. We sought to investigate the outcome of patients treated with TAE in the last 5 years and to look at long-term survival after TAE. Methods: We identified all patients who received TAE within the last 5 years. Using a pre-developed proforma, we looked at case notes and e-records for the number of TAE treatments and checked for symptom improvement, biochemical and radiological response. We also looked at survival time defined as from time TAE to date of death or most recent follow-up. Results: 22 NET patients received TAE (13F/9F) with mean age at diagnosis of 52.9 (1–71). 16 patients had carcinoid, 1 had NET of ovarian origin, 2 pancreatic, 1 stomach. Symptoms were: 15 diarrhoea, 17 flushing, 10 abdominal pain. All patients reported symptom improvement, mean no. of diarrhoea episodes fell from 6.1 (1–10) to 1.8 (0–5), mean no. flushing episodes fell 4.1 (1–10) to 0.6 (0–3). The decrease in 5HIAA in 14 patients was 47.1% (21.6–85.5). Radiological improvement was seen in 18 (81.9%) 1 year survival was 100%. Mean survival after TAE was 25.7 months (8–48). Conclusion: TAE improves symptoms, and there is evidence of improvement in radiology and biochemistry.